The roles of EBV-encoded microRNAs in EBV-associated tumors. (March 2019) - Dong, Min; Chen, Jian-ning; Huang, Jun-ting; Gong, Li-ping; Shao, Chun-kui
Graphical abstract: Abstract: Epstein-Barr virus (EBV) is believed to be a pathogen causing a number of human cancers, but the pathogenic mechanisms remain unclear. An increasing number of studies have indicated that EBV-encoded microRNAs (EBV miRNAs) are expressed in a latency type- and tumor type-dependent manner, playing important roles in the development and progression of EBV-associated tumors. By targeting one or more genes of the virus and the host, EBV miRNAs are responsible for the deregulation of a variety of viral and host cell biological processes, including viral replication, latency maintenance, immune evasion, cell apoptosis and metabolism, and tumor proliferation and metastasis. In addition, some EBV miRNAs can be used as excellent diagnostic, prognostic and treatment efficacy predictive biomarkers for EBV-associated tumors. More importantly, EBV miRNA-targeting therapeutics have emerged and have been developing rapidly, which may open a new era in the treatment of EBV-associated tumors in the near future.